Análisis de la automatización para la gestión del control de personal en la Hacienda "Casa de Tejas". - Salazar Elizondo, Cinthia Yanira (2024)
This case study is based mainly on a systematic analysis for the management of personnel control at the Casa de Tejas farm, since they maintain different processes in the administrative or human talent area manually, making the various activities take longer and are prone to human errors. This gave way to the review of bibliographic sources that helped to know how relevant it is to be at the forefront of technology and currently with significant advances it is very necessary to always maintain correct management in each department so that it is clear, the implementation of a human talent system that generates reports that are easy to manipulate and understand is recommended, that recruits and selects employees, among other activities, and thus manages to make the right decisions that benefit the banana farm.